The Quagmire of Juvenile Delinquency: Perspectives of Inmates and Officers in a Correctional Facility in Accra, Ghana. Issue 2 (1st February 2022) - Dako-Gyeke, Mavis; Adam, Abass; Mills, Abigail A.
ABSTRACT: Drawing on Bronfenbrenner's ecological systems theory, this study explored the experiences and perspectives of juvenile offenders and officers on juvenile delinquency in Accra, Ghana. A descriptive study design with qualitative data collection and analysis methods were employed. A purposive sampling method was used to recruit twenty-six participants, consisting of inmates and officers at a Correctional Facility. Data were gathered through in-depth interviews and the findings showed that parental neglect and abuse; financial constraints; peer influence; and exposure to community social vices influenced juveniles' delinquent behaviors. Additionally, evidence indicated that the inmates benefited from their stay at the correctional facility with respect to their mental health and opportunity to acquire academic knowledge and vocational skills. Based on the findings, suggestions are provided on how juvenile delinquency could be prevented and controlled in Ghana.